Proyecto De Factibilidad Para La Creación De Un Centro Turistico En La Provincia De Zamora Chinchipe - Parroquia Guadalupe - Alverca Abad., Mercy Silvana (2016)
Tourism is an important source of income of the Ecuadorian economy, besides being a source of employment, so that is a distributor of wealth factor, considered one of the most important tools to combat poverty. Zamora Canton and the surrounding region offer a variety of tourist sites in which they can enjoy some quality time with your family and friends. The natural component is rich because of the abundance of attractive flora and fauna. Although the cultural component has an average rating, with promotion and dissemination would be one of the main attractions of this Canton and Parish. Culinary component sector has local dishes made with ingredients typical of the Ecuadorian Amazon. The purpose of this document is to present the design of the project feasibility for the implementation of a resort located in the Guadalupe Parish Canton Zamora Chinchipe. This project is an aid for consultation within the library of the National University of Loja for those interested in the design of feasibility studies. The results thereof are described which were obtained through field research. Families of Zamora Canton as well as tourist families visiting the same surveys were conducted, as well an interview and direct observation was made to bidders for comment on the attraction of Guangzhou, which was of great help to the project development. The steps or components that were taken into account in the preparation of this project itself are: starts with MARKET RESEARCH in which tourism activities taking place mostly in Canton Zamora Chinchipe described - Parish Guadalupe and the number of tourists who visit. For which the sample size where they took into account the population of Canton Zamora with 27.592 residents and 10,106 tourists for a total of 37.698 persons in order to determine the number of surveys which 380 are performed. It should be noted that the surveys were applied to 9.425 families including families tourist said Canton. Potential Demand representing 100% of applicants for the 94% people that if they visit tourist areas, the analysis of the required demands of the project is detailed. The Real Demand for a total of 91% of respondents, while for Effective Demand corresponds to 92% who are willing to visit our resort to be created. And as we bid a total of 20.735 families visiting the resorts, which was one of the determining factors for the number of applicants and bidders will have our project. TECHNICAL STUDY The project characteristics are identified, objectives, mission and vision arise. It describes in detail each of the products and services such as the accommodation, food and recreation, in addition to the installed capacity is 100% with 86 users and Capacity Utilization weekly with 70% representing 60 states that people weekly visit the resort in the first year (2013). Our Resorts is located in Canton Zamora - Guadalupe parish place that has paths first order. Moreover, the administrative organization in which the process for registration of tourist accommodation in the Ministry of Tourism are detailed. It concludes with the organizational structure of the project in which the structural, functional and positional chart to know which functions must be met in the jobs of the company, specifying the profile of each is presented. In another phase of the project we have the FINANCIAL REVIEW in which fixed, deferred assets, working capital or current assets, where it was determined that for the implementation of the project will require an investment of $152.171,03 is described, whose funding will internal by providing two external members with $30.000,00 and funding through the National Development Bank in the amount of $122.171,03 . The sale price is set based on costs and investment costs have been projected through a budget analysis, it was determined in the following products will be offered: in the area of restaurant with a total of $31.117,50 dollars a year income offering breakfast, lunch , snacks and à la carte (tourism courses) as tilapia , frog legs and jerky. In the area of accommodation with an income of $136.800,00 with room service (suite , single, double and triple) and finally we have the service pool for children and adults with a total income of $675,00 U.S. dollars per year . With this analysis and classification of costs over the useful life of the project, with these data was performed breakeven giving 168.592,50 for the first year relative to sales and 56,18% in relation to the capacity is developed installed, for the third year taking 185.823,23 sales with a percentage of installed capacity of 50,79% and finally to the fifth year of 205.662,05 in sales and 46,03% in relation to the installed capacity and the state profit and loss. Finally in the FINANCIAL ASSESSMENT is determined cash flow the first year is projected to 58.857,58 five years. According to the results calculated: the NPV (net present value ) which is $ 93.472,73 which shows that the project is profitable, the IRR (internal rate of return ) is 32,28%, RBC (Relationship Benefit cost) is $1,69 based on whether the result is greater than 1 the project is acceptable in the PRC ( Capital Recovery Period ) identified in that time the investment is recovered it is recovered in 2 years, 11 months, 29 days and 4 hours and AS (Sensitivity Analysis) is evidence that the project supports an increase of 16,30% and a decrease in revenue of 9,72% which means that the project is feasible. Given the necessary considerations and applying the strategies correctly, you can achieve the objectives and to realize not only the project but also convert the tourist center in one of the best of the Parish and why not say the Canton.